Association Between IL-4 and IL-6 Expression Variants and Gastric Cancer Among Portuguese Population - Sampaio,Ana Maria (2015)
Introduction: Multiple studies have reported strong associations between Helicobacter pylori (Hp) inflammation and gastric cancer (GC) development. Altered expressions of pro/anti-inflammatory cytokines have a crucial role in Hp and GC proliferation. Although there are many studies related to cytokines polymorphisms involvement in GC risk, the role of Interleukin-4 (IL-4) and Interleukin-6 (IL-6) in gastric inflammation process is not yet clarified. Aim: This study aimed to investigate the impact of common IL-4 and IL-6 polymorphisms in GC development risk among Portuguese population. Methods: A total of 100 GC biopsies (50 with intestinal type, IGC, 50 with diffuse type, DGC) and 50 chronic gastritis cases, used as control group, were included in this case-control study. IL-4 and IL-6 common polymorphisms were genotyped by PCR-SSP, using commercially available kits. Results: IL-4 low producer genotypes, IL-4-590TT (OR = 6.7; 95% CI 1.4-32.4) and IL-4-1098GG (OR = 4.4; 95% CI 1.7-16.9) were found associated with IGC and DGC, respectively. We also verified that IL-4 TTT haplotype was linked with both IGC (OR = 5.8; 95% CI 2.3-14.4) and DGC (OR = 2.3; 95% CI 1.0-5.5) groups. Concerning IL-6 results, IL-6-174CG genotype showed a higher prevalence among IGC cases (OR = 7.3; 95% CI 2.7-20.3), and IL-6-174CC (OR = 3.8; 95% CI 1.7-8.7) showed upper prevalence within DGC subjects. Finally, IL-6-174/nt565CG haplotype showed a significant association with both IGC (OR = 7.3; 95% CI 2.7-20.3) and DGC (OR = 7.9; 95% CI 4.2-14.9). Conclusion: IL-6 and IL-4 expression variants seem to have an important role in GC risk mechanisms. This study provides preliminary evidence that IL-4 and IL-6 polymorphisms, although not directly linked to the disease, may be useful tools in the study of this multifactorial disease.